2020
DOI: 10.3390/v12090916
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Newcastle Disease Viruses Isolated from Chickens in Tanzania and Ghana

Abstract: Newcastle disease (ND) is one of the most challenging infectious diseases affecting poultry production in Africa, causing major economic losses. To date, Newcastle disease virus isolates from several African countries have been grouped into class II NDV genotypes I, IV, V, VI, VII, XI, XIII, XIV, XVII, XVIII and XXI. Although ND is endemic in many African countries, information on circulating genotypes is still scarce. In Tanzania, outbreaks with genotypes V and XIII have been reported. In West and Central Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
3
19
1
Order By: Relevance
“…Phylogenetic analyses, of the three Iranian Usachev et al, 2006). To date, the circulation of genotypes of NDV strains XIIIa, XIIId, VIIj and VIId in commercial poultry (Abah et al, 2020;da Silva et al, 2020), VI in domestic pigeons (da Silva et al, 2020;Rezaei Far et al, 2017) and VII in domestic poultry (Sabouri et al, 2016) et al, 2013). Munir et al (2018) reported the similarity of phylogenetic analysis between HN gene and F gene in NDVs that is following our results in this study (Munir & Shabbir, 2018;Soltani, Peighambari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses, of the three Iranian Usachev et al, 2006). To date, the circulation of genotypes of NDV strains XIIIa, XIIId, VIIj and VIId in commercial poultry (Abah et al, 2020;da Silva et al, 2020), VI in domestic pigeons (da Silva et al, 2020;Rezaei Far et al, 2017) and VII in domestic poultry (Sabouri et al, 2016) et al, 2013). Munir et al (2018) reported the similarity of phylogenetic analysis between HN gene and F gene in NDVs that is following our results in this study (Munir & Shabbir, 2018;Soltani, Peighambari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes XII, XIII and XIV have ancestors similar to genotype VII that produce different distinct lineages in the course of its evolution (Orynbayev et al., 2018 ; Ramey et al., 2013 ; Usachev et al., 2006 ). To date, the circulation of genotypes of NDV strains XIIIa, XIIId, VIIj and VIId in commercial poultry (Abah et al., 2020 ; da Silva et al., 2020 ), VI in domestic pigeons (da Silva et al., 2020 ; Rezaei Far et al., 2017 ) and VII in domestic poultry (Sabouri et al., 2016 ) have been proven in Iran. These data show that VII and XIII are among the most predominant NDV subgenotypes circulating in Iran between 1995 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…None of these mutations affect the specifics residues of Malagasy strains (genotype XI), as reported by Maminiaina in 2011 [32]. Furthermore, none of them correspond to the characteristic mutations of the new genotypes such as XIV, XVII and XVIII [33][34][35][36]. Thus, the identification of these mutations raises an alarm about the existence of a progressive evolution in genotype XI originating from Madagascar.…”
Section: Discussionmentioning
confidence: 86%
“…A previous study grouped NDV isolates collected in several African countries according to the updated NDV classification system [ 37 ] and identified up to three genotypes in Tanzania (V, VII, and XIII) [ 13 , 14 , 38 ] and one genotype in Ghana (XVIII) [ 13 , 14 ]. However, within each genotype class consists a collection of NDV strains and it is likely that, even in Ghana, different strains were present in the different replicates.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their pathological type, strains of NDV are classified into lentogenic, mesogenic, and velogenic strains [ 8 , 9 , 10 ]. Velogenic strains cause severe disease and are endemic and responsible for high mortality in poultry in the developing countries of Africa [ 11 , 12 , 13 ], Asia [ 14 ], and South America. Outbreaks are often devastating, and a velogenic strain can cause up to 100% mortality in chicken flocks, resulting in severe economic losses for families.…”
Section: Introductionmentioning
confidence: 99%